HIV in the heartland: negotiating disclosure, stigma, & the HIV community - Donley, Sarah B. (Kansas State University, 2009)
Even after 28 years the AIDS epidemic continues to affect the American population and HIV/AIDS remains a social problem. Living with HIV affects every aspect of an individual’s life. It involves a personal negotiation at the onset of diagnosis, a social negotiation when one decides to disclose to others, and finally, a communal negotiation when individuals seek formal support via ASOs (AIDS service organizations), and/or informal support through family members and friends. The purpose of this research is to investigate these negotiations over the course of HIV infection, how these processes inform decisions to disclose, how stigma influences lived experiences, and the importance of the HIV community. The data come from eighteen HIV+ individuals, ten men and eight women, living in various locations throughout the Midwest. Drawing on the experiences of these men and women, I explore reactions after diagnosis, disclosure patterns, experiences of stigma, and the importance of the HIV community.
Keywords: HIV/AIDS; Stigma; Midwest; Community; Disclosure; Sociology, General (0626)